PWE-118 Metachronous Cancers Following Segmental or Extended Colectomy in Lynch Syndrome: A Systematic Review & Meta-Analysis. (17th August 2016) - Malik, SS; Lythgoe, M; Monahan, KJ
Abstract : Introduction: Around 5% of colorectal cancers are due to mutations within DNA mismatch repair genes, resulting in Lynch Syndrome (LS). These mutations have a high penetrance (85–90%), with early onset of colorectal cancer at an average age of 45 years. The main surgical management options are either a segmental or extensive colectomy. Currently there is no unified agreement as to which management strategy is superior due to the limited conclusive empirical evidence available. A systematic review and meta- analysis to evaluate the risk of metachronous colorectal cancer (MCC) and mortality in LS following segmental and extensive colectomy. Methods: A systematic review of the Pubmed database was conducted. Studies were included/ excluded based on a pre-specified criteria. In order to assess the risk of MCC and mortality attributed to segmental or extensive colectomies, pooled odds ratios (OR) were calculated and corresponding 95% confidence intervals (CI). Publication bias was investigated using funnel plots. Statistical analysis was conducted using the R program (version 3.2.3). Results: The literature search identified eighty-five studies. After further analysis nine studies were eligible for inclusion in this study. Pooled data identified 1429 patients followed up for a mean of 103.1 months with a mean age of onset of 43.3 years of age. 1135 patients underwent segmental colectomies with risk of MCC in this group of 22.0% at the end of follow-up. 294 patients had extensive colectomies with a MCC risk of 4.7% (0% in those with a panproctocolecomy). A segmental colectomy was significantly associated with an increased risk of MCC (OR = 4.47; 95% CI: 2.68–7.45; Figure 1), but no significant association with mortality was identified (OR = 1.65; 95% CI: 0.71–3.82). Conclusion: In LS, segmental colectomy results in a significant increased risk of developing MCC. Despite the choice of segmental or extensive colectomies having no statistically significant impact on mortality, the choice of initial surgical management can impact a patient's requirement for further surgery. An extensive colectomy can result in decreased need for further surgery; reduced hospital stays and reduced costs. The significant difference in the risk of MCC, following segmental or extensive colectomies should be discussed with patients when deciding appropriate management. Disclosure of Interest: None Declared